The Type of Breast Reconstruction May Not Influence Patient Satisfaction in the Chinese Population: A Single Institutional Experience - Yang, Benlong; Li, Lin; Yan, Wenhui; Chen, Jiaying; Chen, Ying; Hu, Zhen; Liu, Guangyu; Shen, Zhenzhou; Shao, Zhimin; Wu, Jiong (PLOS ONE, 2015)
Background The goal of this study was to evaluate patient satisfaction with four common types of breast reconstruction performed at our institution: latissimus dorsi myocutaneous (LDM) flap reconstruction with or without implants, pedicled transverse rectus abdominis musculocutaneous (TRAM) flap reconstruction, and free deep inferior epigastric perforator (DIEP) flap reconstruction. Methods A custom survey consisting of questions that assessed general and aesthetic satisfaction was sent to patients who had undergone breast reconstruction in the last 5 years. The clinical data and details of the surgery were also collected from the patients who returned the surveys. We compared satisfaction rates across the four breast reconstruction types and analyzed the effects of various factors on overall general and aesthetic satisfaction rates using a binary logistic regression model. Result A total of 207 (72%) patients completed the questionnaires. Overall, significant differences in general and aesthetic satisfaction among the four procedures were not observed. A multivariate analysis revealed that the factor “complications” (p = 0.001) played a significant role in general satisfaction and that the factors “> 2 years since reconstruction” (p = 0.043) and “age > 35 years” (p = 0.05) played significant roles in overall aesthetic satisfaction. Conclusion The present study demonstrated that the type of breast reconstruction might not influence satisfaction in Chinese patients.